2005
DOI: 10.1021/jm058184l
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of Phe6, Phe7, and Phe11ofd-Trp8-Somatostatin-14 withl-Pyrazinylalanine. Predicted and Observed Effects on Binding Affinities at hSST2 and hSST4. An Unexpected Effect of the Chirality of Trp8on NMR Spectra in Methanol

Abstract: An alanine scan performed in the 1970s suggested that Phe(6) and Phe(11) are required for the binding of somatostatin (SRIF-14). Molecular modeling studies and replacement of Phe(6) and Phe(11) with a cystine bridge affording ligands with the retention of high biological activity, however, led to the alternate conclusion that Phe(6) and Phe(11) stabilize the bioactive conformation of SRIF-14. Subsequent studies revealed that Phe(11) shields Phe(6) in a "herringbone" arrangement. More recently, a report from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…As expected, the half‐life of peptide 5 with L ‐Trp8 is only twice as high as that of somatostatin. The surprisingly the long half‐life of analogue 3 (Msa in position 11) relative to peptides 2 and 4 , may corroborate the fact that the unnatural aromatic residue in position 11 shields the residue at position 6, as previously suggested 10b…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…As expected, the half‐life of peptide 5 with L ‐Trp8 is only twice as high as that of somatostatin. The surprisingly the long half‐life of analogue 3 (Msa in position 11) relative to peptides 2 and 4 , may corroborate the fact that the unnatural aromatic residue in position 11 shields the residue at position 6, as previously suggested 10b…”
Section: Methodssupporting
confidence: 81%
“…This interaction could enable in the stabilization of some of the biologically active conformations of the hormone. A few years later, the same authors detected the Phe6–Phe11 interaction by NMR spectroscopy,10a and hypothesized that it should be perpendicular (edge‐to‐face) rather than parallel (face‐to‐face) 10a,b. However, van Binst and co‐workers subsequently reported that they were unable to observe the Phe6–Phe11 interaction by NMR spectroscopy (either in aqueous solution or in methanol) and that the only interaction that they could observe was that between Phe6 and Phe7 11a,b.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the C-terminus of peptides active at class B GPCR act as a docking site to initiate the helix formation, and the N-terminal residues are responsible for the activation of the receptors (Parthier et al, 2009; Karnik et al, 2003). Conversely peptides active at class A GPCR (including the C3aR1) (Beck-Sickinger et al, 1994; Neelamkavil, et al, 2005) as well as other peptides of the granin family (Bartolomucci et al, 2011), do not show a common binding mechanism. The hot spots for TLQP-21 activity reside at the C-terminus.…”
Section: Discussionmentioning
confidence: 99%
“…The latter will have implications in the design of synthetic ligands that mimic α-helical conformations to target C3aR1 and activate lipolysis to treat obesity and obesity-related disorders. Synthetic molecules designed to target GPCRs have already been developed into potent agonists and antagonists by engineering lactam-bridges promoting α-helical structures (Neelamkavil et al, 2005; Ammoun et al, 2003; Grace et al 2007; Murage et al, 2008; Pellecchia et al, 2008). The mouse TLQP-21 sequence represents a molecular template for designing new analogues of this peptide that can serve as agonists or antagonists for C3aR1 having important implication for obesity (Possenti et al, 2012) diabetes (Stephens et al, 2012), hypertension (Fargali et al, 2014), pain (Fairbanks et al, 2014) and potentially immune functions.…”
Section: Discussionmentioning
confidence: 99%
“…However, to the best of our knowledge, the effect of introducing fluorinated Phe residues in the context of Somatostatin has not been addressed to date 27 . One of the few reports of Somatostatin analogs containing electron-poor aromatic residues as Phe isosteres was done by Hirschmann and co-workers 28 , who synthesized analogs containing L-pyrazinylalanine (Pyz).…”
mentioning
confidence: 99%